Development of segmented flow crystallisers for in situ X-ray diffraction analysis - Galtry, Elizabeth Sarah (2025)
The study of crystallisation through in situ analysis methods is key to elucidating the crystallisation processes of polymorphic materials. This thesis presents research on the development of in situ X-ray diffraction (XRD) techniques for the study of segmented flow crystallisation. This work was carried out as a joint studentship between University of Nottingham and Diamond Light Source, the UK’s national synchrotron research facility.